?2-Coordination of Chlorobenzenes to Rhenium Fragment Cp*Re(Co)2: Chemical and Photochemical Syntheses of Cp*Re(Co)2(?2-C6h6-Ncl N) - Godoy-Gonzalez, F; Godoy-Gonzalez, F (2011)
Sin Editorial Disponible